RELATIONSHIP OF RESPONSIVE, EFFICIENCY AND ACCOUNTABILITY TO GOOD CORPORATE GOVERNANCE (LITERATURE REVIEW STUDY) - Ricardo Ricardo (Dinasti Publisher, 2022)
The Literature Review article on the Relationship of Responsiveness, Efficiency and Accountability to Good Corporate Governance is an article to build a research hypothesis on the relationship between variables that will be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Responsiveness relates to Good Corporate Governance; 2) Efficiency relates to Good Corporate Governance; and 3) Accountability related to Good Corporate Governance. Apart from these 3 exogenous variables that affect the endogenous variable of Good Corporate Governance, there are other factors including participation, transparency, inclusion, and following the rules.